Hydroxysafflor Yellow A Inhibits LPS-Induced NLRP3 Inflammasome Activation via Binding to Xanthine Oxidase in Mouse RAW264.7 Macrophages - Xiaolong Xu; Yuhong Guo; Jingxia Zhao; Ning Wang; Junying Ding; Qingquan Liu (Mediators of Inflammation)
Hydroxysafflor yellow A (HSYA) is an effective therapeutic agent for inflammatory diseases and autoimmune disorders; however, its regulatory effect on NLRP3 inflammasome activation in macrophages has not been investigated. In this study, we predicted the potential interaction between HSYA and xanthine oxidase (XO) via PharmMapper inverse docking and confirmed the binding inhibition via inhibitory test (IC50 = 40.04 μM). Computation docking illustrated that, in this HSYA-XO complex, HSYA was surrounded by Leu 648, Leu 712, His 875, Leu 873, Ser 876, Glu 879, Phe 649, and Asn 650 with a binding energy of −5.77 kcal/M and formed hydrogen bonds with the hydroxyl groups of HSYA at Glu 879, Asn 650, and His 875. We then found that HSYA significantly decreased the activity of XO in RAW264.7 macrophages and suppressed LPS-induced ROS generation. Moreover, we proved that HSYA markedly inhibited LPS-induced cleaved caspase-1 activation via suppressing the sensitization of NLRP3 inflammasome and prevented the mature IL-1β formation from pro-IL-1β form. These findings suggest that XO may be a potential target of HSYA via direct binding inhibition and the combination of HSYA-XO suppresses LPS-induced ROS generation, contributing to the depression of NLRP3 inflammasome and inhibition of IL-1β secretion in macrophages.